11b+6=-27

Simple and best practice solution for 11b+6=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11b+6=-27 equation:


Simplifying
11b + 6 = -27

Reorder the terms:
6 + 11b = -27

Solving
6 + 11b = -27

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 11b = -27 + -6

Combine like terms: 6 + -6 = 0
0 + 11b = -27 + -6
11b = -27 + -6

Combine like terms: -27 + -6 = -33
11b = -33

Divide each side by '11'.
b = -3

Simplifying
b = -3

See similar equations:

| 3n-8n=-6n-3 | | 5(x+y)-5(x-y)= | | 3+7x-5x=-9 | | 5+c=6 | | 10g+3=5g-27 | | x+8=-10-8x | | 6+3-1= | | -5(4x-2)=2(3+6x) | | 8+b=16 | | 4y-12=-12+4y | | 7-5(5a-4)=6-4a | | -6k-7k= | | 10-a=12 | | 14x(2)+5-[7(x(2)+-2)+4]= | | 21x^2+12x-1= | | 5(x-7)+2=4 | | 1/2(x-3)+(3/2-x)=5x | | 5x+2y=-9 | | 7n+1.3=22.3whatisn | | 19-3n=5n-13 | | 36+62= | | 3c-11=7c+19 | | 3-7x-x=-1 | | 6(1+6b)minus-8=106 | | -5x+12=6 | | -11-5a=6(5a+14) | | 8(3x+5)-(7x-2)=8 | | -3-6x=-5-4x | | 6(1+6b)-8=106 | | 2r=8r-30 | | 8-3a=2 | | 3r+2=3r+2 |

Equations solver categories